2012
DOI: 10.1186/1754-6834-5-62
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane bagasse pretreatment using three imidazolium-based ionic liquids; mass balances and enzyme kinetics

Abstract: BackgroundEffective pretreatment is key to achieving high enzymatic saccharification efficiency in processing lignocellulosic biomass to fermentable sugars, biofuels and value-added products. Ionic liquids (ILs), still relatively new class of solvents, are attractive for biomass pretreatment because some demonstrate the rare ability to dissolve all components of lignocellulosic biomass including highly ordered (crystalline) cellulose. In the present study, three ILs, 1-butyl-3-methylimidazolium chloride ([C4mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…The conversion yield for cellulose was 72% on the sample treated with H 2 SO 4 and 1% NaOH which was comparatively much better as compared to the 22% in case of untreated sample [54]. Similarly, Karatzos et al [55] observed the compositional and structural characteristics of sugarcane bagasse after pretreating it with three of the ionic liquids: 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride and 1-ethyl-3-methylimidazolium acetate. The concerned study found 1-ethyl-3-methylimidazolium acetate to be the most effective in delignification and also in saccharification yields.…”
Section: Enzymatic Hydrolysismentioning
confidence: 89%
“…The conversion yield for cellulose was 72% on the sample treated with H 2 SO 4 and 1% NaOH which was comparatively much better as compared to the 22% in case of untreated sample [54]. Similarly, Karatzos et al [55] observed the compositional and structural characteristics of sugarcane bagasse after pretreating it with three of the ionic liquids: 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride and 1-ethyl-3-methylimidazolium acetate. The concerned study found 1-ethyl-3-methylimidazolium acetate to be the most effective in delignification and also in saccharification yields.…”
Section: Enzymatic Hydrolysismentioning
confidence: 89%
“…The compositions of untreated bagasse and bagasse pretreated in the Mackay Renewable Biocommodities Pilot Plant with dilute H 2 SO 4 steam explosion, dilute NaOH steam explosion, and glycerol/HCl steam explosion under conditions described in our previous study [23] are presented in Table 1. The compositions of untreated (depithed) and bagasse pretreated at the laboratory scale with acidified EC/EG [38], BMIMCl [39], and ballmilling are presented in the same table. Percentages of glucan (cellulose), xylan (the majority of hemicellulose), lignin, and ash were calculated on a dry mass basis.…”
Section: Pretreatment and Characterisation Of Bagassementioning
confidence: 99%
“…The EC/EG pretreatment was undertaken at a solidto-liquid ratio of 4:1 (w/w) in the presence of 1.2% (w/w) H 2 SO 4 at 90°C for 30 min using the method described by Zhang et al (2013) [38]. The ionic liquid pretreatment was undertaken with BMIMCl containing 0.7% (w/w) water at a 10:1 (w/w) liquid-to-solid ratio at 150°C for 1 h using the method described by Karatzos et al (2012) [39]. Ball-milling was achieved using a Pulverisette 6 (Fritsch, GmbH) at ambient temperature using 10 min on/off for a total of 16 h. All pretreated bagasse samples were washed extensively with deionised water and freeze dried.…”
Section: Pretreatment Of Sugar Cane Bagassementioning
confidence: 99%
“…switchgrass), agricultural or forestry residues (e.g. sugarcane bagasse), present an abundant renewable energy resource [1]. Along with the decreasing reserves of fossil fuel resources and the increasing of world energy demand, the utilization of biomass as renewable and sustainable feedstock to produce alternative fuels and chemicals have attracted much interest in recent years.…”
Section: Introductionmentioning
confidence: 99%